2012
DOI: 10.1007/s10162-011-0309-9
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Kainate Receptors

Abstract: Synaptic transmission between the cochlear hair cell and its afferent fiber is mediated by glutamate receptors. While kainate receptors are known to be present in the spiral ganglion, little is known of their distribution or functional role. We have detected all five kainate receptor subunits in the mouse cochlea with quantitative RT-PCR and with immunohistochemistry. We observed kainate receptors on afferent terminals co-localized with α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…In contrast, Peppi et al (2012) showed that some puncta representing each of the 5 KAR subunits could colocalize with GluA2 puncta at the base of the IHCs of CBA/CaJ mice. We found that GluA2-immunoreactivity (using the same monoclonal antibody that was used in Peppi et al, 2012) produced some puncta that do not colocalize with the ribbon and PSD markers.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In contrast, Peppi et al (2012) showed that some puncta representing each of the 5 KAR subunits could colocalize with GluA2 puncta at the base of the IHCs of CBA/CaJ mice. We found that GluA2-immunoreactivity (using the same monoclonal antibody that was used in Peppi et al, 2012) produced some puncta that do not colocalize with the ribbon and PSD markers.…”
Section: Discussionmentioning
confidence: 72%
“…Based on the X-gal staining pattern in cochleae from GluK5 KO mice as well as what is known from the literature (Peppi et al, 2012), we hypothesized that GluK5 and other KAR subunits (Lerma and Marques, 2013) are expressed in the postsynaptic membrane of afferent terminals in IHCs and also in both pre- and postsynaptic membranes of afferent terminals in OHCs.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Measurements were made from the right ear of female Mongolian gerbils weighing between 45 and 70 g. Ouabain, which abolishes auditory nerve responses while maintaining hair cell responses (e.g., Schmiedt et al, 2002;Lang et al, 2005;Peppi et al, 2012;Yuan et al, 2014) was used to quantify the extent to which neural excitation contributes to f Tr . All experiments were acute in that on a given day a pharmaceutical treatment was applied, an experiment performed, and the animal was sacrificed.…”
Section: A Overviewmentioning
confidence: 99%